PENGARUH MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA BAAMBOOZLE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII PADA MATERI BENTUK ALJABAR DI SMP NEGERI 1 SUWAWA - Nazwa; Novianita Achmad; Aulia Irfah; Evi P. Hulukati; Nursiya Bito; Bertu Rianto Takaendengan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Cooperative Learning model of the Teams Games Tournament (TGT) type assisted by Baamboozle media on students' mathematics learning outcomes in the topic of Algebraic Expressions. The study employed an experimental method using a Post-test Only Control Group Design. The research sample consisted of 21 students from class VII-C as the experimental group and 20 students from class VII-D as the control group, selected through a cluster random sampling technique. Data were collected using a cognitive learning outcomes test and analyzed using an independent sample t-test. The results showed that the calculated t-value (t = 3.275) was greater than the critical t-value (t = 1.68488) at the 0.05 significance level, indicating that H₀ was rejected and H₁ was accepted. Furthermore, the effect size calculated using Cohen’s d formula was 1.023, which falls into the high category. Therefore, it can be concluded that the Cooperative Learning model of the Teams Games Tournament (TGT) type assisted by Baamboozle media has a significant positive effect on students' mathematics learning outcomes in the topic of Algebraic Expressions among seventh-grade students at SMP Negeri 1 Suwawa. Keywords: Teams Games Tournament (TGT), Baamboozle, Learning Outcomes, Algebraic Expressions.